In memoriam Benjamin Ferencz - Infante Caffi, María Teresa (Revista Tribuna Internacional, 2023)
The Department of International Law of the University of Chile Law School dedicates these words to the lawyer and internationalist Benjamin Ferencz. He passed away in Florida, United States, on the 7th of April 2023. He was the last surviving prosecutor of the Einsatzgruppen Case before the International Tribunal of Nuremberg (1945-1946)